BIOFILTER AEROB MEDIA KALDNESS DALAM MENURUNKAN KADAR BOD, COD DAN TSS LIMBAH CAIR RUMAH MAKAN - Yuli Sifaul Ummah; Iva Rustanti Eri Wardoyo; Pratiwi Hermiyanti (GEMA LINGKUNGAN KESEHATAN, 2020)
Restaurant  liquid waste is waste originating from the operational activities of a restaurant which is largely unprocessed, but disposed of directly to the receiving water body. This study aims to reduce Biogeochemical Oxygen, COD (Chemical Oxygen Demand), TSS (Total Suspended Solid) in restaurant wastewater by processing aerobic biofilter using caldness media.            This type of research is an experiment with pretest-posttest research design. In this design, it is done to find out the initial condition of the subject before being treated so that it can determine the condition of the subject under study before the treatment can be compared or seen changes in the analysis of data used using the Pretest-Posttest test in order to determine the differences in 2 treatment groups.            The results of examination of the levels of BOD, COD and TSS before treatment with the BOD Caldness medium were 333,822,00 mg/ liter, COD was 575,535,00 mg/ liter and TSS was 580,136,00 mg/ liter. After treatment with a medium of Caldness of BOD of 580 mg / liter, COD of 1019 gr / liter, and TSS of 430 gr / liter.            The conclusion of this study is that the results obtained after processing used Kaldnes media were very  in reducing BOD by 99.98%, COD by 99.82% and TSS by 99, 92% in restaurant wastewater treatment.Keywords: Restaurant Wastewater, BOD, COD and TSS